SQLite Sebagai Pengganti Lucene.Net pada Pencarian Produk Toko Online - Imam Farisi; Mukhaimy Gazali; Rudy Anshari (Universitas Muhammadiyah Riau, 2020)
A business institution can promote their products in its online shop. With the promotion of online stores, consumers can find out which products are sold at the store. Consumers who are looking for a product can search based on various attributes of goods that are scattered in various fields in the database table, and can even be spread across different tables. All attributes that point to an item are collected in one document which will be searched using the Full Text Search system. Two alternatives to the Full Text Search system were selected; Lucene.Net and Sqlite Full Text Search. Before actually being used, these two search system alternatives were tested first. In document storage size, Lucene.Net is superior by 6.78 times. The speed of writing Sqlite search documents is superior by between 1,875 times to 5,197 times. In terms of key search speed, Lucene.Net was superior by between 1,169 and 1,698 times. Based on the consideration of the speed and development of Lucene.Net Core which is still in beta stage, Sqlite Full Text Search is suitable for use in the product search process in the Online Store.